Point Mutations at gyrA and gyrB Genes of Levofloxacin Resistant Helicobacter pylori Strains and Dual Resistance with Clarithromycin - Ziver-Sarp, Tevhide; Yuksel-Mayda, Pelin; Saribas, Suat; Demiryas, Suleyman; Gareayaghi, Nesrin; Ergin, Sevgi; Kocazeybek, Bekir (Clin Lab Publ, 2021)
Background: Spontaneous point mutations in genes encoding gyrA/B subunits of DNA gyrase are responsible for fluoroquinolone resistance. We aimed to determine the clarithromycin and levofloxacin resistance phenotypically in H. pylori strains and to investigate the mutations responsible for levofloxacin resistance and the effects of these mutations on dual antibiotic resistance. Methods: A total of 65 H. pylori isolates were included. The E-test method was used for the clarithromycin and le-vofloxacin antimicrobial susceptibility test. Real-time PCR was used to detect the point mutations. Results: Twenty-four (36.9%) of 65 H. pylori strains were phenotypically resistant to clarithromycin and 14 (21.5%) to levofloxacin. The phenotypic levofloxacin resistance rate of strains with Asn87Lys and Asp91Asn mu-tations were significantly higher (gyrA gene) (p < 0.05). The phenotypic levofloxacin resistance rate of strains with Arg484Lys and Asp481Glu mutations were significantly higher (gyrB gene) (p < 0.05). The Asn87Lys mutation in-creased the risk of phenotypes being resistant to levofloxacin 70.156 times and Asp91Asn mutation increased 125,427 times higher. Seven (10.8%) of 65 H. pylori strains showed dual resistance to both levofloxacin and cla-rithromycin. The rate of being dual resistant with A2143G mutation (clarithromycin resistance) was found to be significantly higher (p < 0.05). Conclusions: The Asn87Lys and Asp91Asn mutations in the gyrA gene had a phenotypically enhancing effect on levofloxacin resistance, while the presence of Asp481Glu and Arg484Lys mutations in the gyrB gene did not. The existence of dual resistance was developed with the increase in clarithromycin and levofloxacin resistance rates. (Clin. Lab. 2021;67:2369-2377. DOI: 10.7754/Clin.Lab.2021.210843)
Keywords: point mutations; H; pylori; gyrA; gyrB gene; levofloxa-cin resistance; dual resistance